Post-fire seismic behavior of reinforced concrete structural walls. (1st August 2018) - Ni, Shuna; Birely, Anna C.
Highlights: Numerical study of post-fire seismic performance of reinforced concrete (RC) walls. Fire exposure degrades load-bearing capacity and lateral stiffness. Fire effect on deformation capacity is best characterized by curvature. Fire exposure may alter the damage patterns at failure. Axial load and wall thickness have the greatest influence on the performance. Abstract: A potential but infrequently studied hazard is the sequential occurrence of earthquakes and fires. Fire hazards following an earthquake can be significant due to increased likelihood of fires igniting, increased demands on firefighting resources, and potential obstacles to timely response. Increased ignitions and longer burn times can have significant structural impacts on reinforced concrete (RC) structures which are usually considered to have superior performance in a fire. The impact of this fire induced structural damage on the lateral load resistance of RC structures, particularly RC structural walls, is not well understood but may be critical in the event of aftershocks and/or future earthquakes. Given the severity of the consequences of reduced lateral load resistance, it is important for engineers to better understand fire-earthquake hazards in RC walls. This paper presents numerical studies to investigate the impact of fire damage on the lateral load resistance of flexure-controlled RC structural walls, including a parametric study to identify influential wall characteristics. Results indicate that fire damage decreases the load-bearing capacity and the stiffness of RC walls under reversed-cyclic loads. Curvature is shown to be a better indication of fire induced failure. At failure, damage may shift to the web of a wall after fire exposure becomes more severe. Wall characteristics which significantly influence the residual wall response quantities were identified to be wall thickness, boundary element length, and axial load ratio.